2004
DOI: 10.1038/sj.tpj.6500229
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of synaptic vesicle proteins by antidepressant drugs

Abstract: Synaptic vesicle proteins (SVP) play a critical role in neurotransmitter release and neural plasticity, and have been implicated in the pathophysiology of psychiatric disorders such as depression. Antidepressant drugs not only alter the level of neurotransmitters, but also modulate de novo gene transcription and synthesis of proteins involved in neural plasticity. In order to investigate the effects of antidepressant compounds on SVP-mRNA levels, the expressions of synaptophysin, synaptotagmin, VAMP, and synap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
1
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 25 publications
5
25
1
3
Order By: Relevance
“…The effects of mifepristone on the mRNA level of synapsin I are not quite the same as tranylcypromine. Mifepristone decreases synapsin I in DG/CA3 and increases it in CA1 subfield in hippocampus, whereas tranylcypromine decreases synapsin I in both DG/ CA3 and CA1 subfields (Rapp et al, 2004). This difference may be explained by using different animal models.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The effects of mifepristone on the mRNA level of synapsin I are not quite the same as tranylcypromine. Mifepristone decreases synapsin I in DG/CA3 and increases it in CA1 subfield in hippocampus, whereas tranylcypromine decreases synapsin I in both DG/ CA3 and CA1 subfields (Rapp et al, 2004). This difference may be explained by using different animal models.…”
Section: Discussionmentioning
confidence: 95%
“…There are a few reports about the effects of antidepressants on synapsin I in rat hippocampus. Chronic treatment with tranylcypromine, but not desipramine or fluoxetine, decreases synapsin I mRNA expression in rat hippocampal DG, CA3, and CA1 (Rapp et al, 2004), and imipramine or fluvoxamine decreases synapsin I immunoreactivity in rat hippocampus (Iwata et al, 2006). Another study showed that injecting rats with lithium for 30 days produces no changes in total synapsin in the hippocampus (Vawter et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As chronic stress also induces dendritic atrophy and spine loss in mPFC pyramidal neurons (Radley et al, 2004;Wellman, 2001), it is feasible that fluoxetine treatment may induce the opposite effect. The fact that chronic fluoxetine treatment induces an increase in synaptohysin (a protein specific of synapses) expression in the cerebral cortex (Rapp et al, 2004), gives support to this hypothesis. However, studies on the structure of mPFC neurons after antidepressant treatment should be performed to clarify this matter.…”
Section: Involvement Of Psa-ncam Expression In Mpfc Neuronal Structurmentioning
confidence: 90%
“…Interestingly, chronic exposure to second-generation antispychotics olanzapine or risperidone enhances PSA-NCAM expression in the PFC, but not in the hippocampus, suggesting that modulation of cell adhesion protein in the hippocampus may be specific to the mechanism of action of ADs [152,153]. Moreover, an increased expression of synaptophysin, a glycoprotein localized in presynaptic vesicle membranes required for docking and fusion of neurotransmitter-containing synaptic vesicles as well as endocytosis [154], was observed in hippocampus and/or cerebral cortex of rats chronically treated with the MAOI tranylcypromine, the TCA amitriptyline or the SSRI fluoxetine [148,155,156]. Also, Arc (Activity-regulated, cytoskeletalassociated protein), a highly expressed protein in dendrites and postsynaptic densities [157] is implicated in LTP and spine size and type [158][159][160].…”
Section: Synaptic Plasticity and Synaptogenesismentioning
confidence: 99%